Investigation and analysis of sleep and mental health status among MEFCs - Yu, Kangying; Song, Shaozheng; Wu, Liu; Chen, Zhe (Frontiers in Psychiatry, 2025)
ObjectiveTo investigate the sleep status and mental health of migrants elderly who followed their children (MEFC) and analyze the influencing factors.MethodsA total of 583 MEFCs were surveyed using a general demographic questionnaire, the Pittsburgh Sleep Quality Index (PSQI) scale, and the Symptom Checklist 90 (SCL90) scale.ResultsThe mean PSQI score for MEFCs was 6.98 ± 0.17, and the average SCL90 score was 64.06 ± 2.03. Multiple linear regression analysis indicated that health status and adaptation to the migration destination were associated with PSQI scores (P < 0.05). Health status, adaptation to the migration destination, and family harmony were associated with SCL90 scores (P < 0.05). The association coefficient between the total PSQI and SCL90 scores was r=0.462 (P < 0.05).ConclusionThe sleep and mental health of MEFCs were at a normal level. Health status and adaptation influenced sleep status, while health status, adaptation, and family harmony impacted mental health. However, the association between mental health and sleep status was weak.